Cycling science - Zabala, Mikel 1974-; Cheung, Stephen S. 1968- (Champaign, IL Human Kinetics, 2017)
Finally, the authoritative resource that serious cyclists have been waiting for has arrived. The perfect blend of science and application, Cycling Science takes you inside the sport, into the training room and research lab, and onto the course. A remarkable achievement, Cycling Science features the following: Contributions from 43 top cycling scientists and coaches from around the world; The latest thinking on the rider-machine interface, including topics such as bike fit, aerodynamics, biomechanics, and pedaling technique; Information about environmental stressors, including heat, altitude, and air pollution; A look at health issues such as on-bike and off-bike nutrition, common injuries, fatigue, overtraining, and recovery; Help in planning training programs, including using a power meter, managing cycling data, off-the-bike training, cycling specific stretching, and mental training; The latest coaching and racing techniques, including pacing theories, and strategies for road, track, MTB, BMX, and ultra-distance events. In this book, editors and cycling scientists Stephen Cheung, PhD, and Mikel Zabala, PhD, have assembled the latest information for serious cyclists.
Part I. The Cyclist -- Chapter 1. The Cyclist's Physique / Paolo Menaspa ̀and Franco Impellizzeri -- Chapter 2. Cycling Physiology and Genetics / Stephen S. Cheung -- Part II. The Bike -- Chapter 3. Bicycle Design / Larry Ruff -- Chapter 4. Frame Materials and Geometry / Larry Ruff -- Chapter 5. Saddle Biomechanics / Daniel Schade -- Part III. The Human-Machine Interface -- Chapter 6. Biomechanics of Cycling / Rodrigo Rico Bini -- Chapter 7. The Science of Bike Fit / Rodrigo Rico Bini -- Chapter 8. Bike Fit and Body Positioning / Todd M. Carver -- Chapter 9. The Aerodynamic Rider / Andy Froncioni -- Chapter 10. Pedaling Technique and Technology / Thomas Korff, Marco Arkesteijn, and Paul Barratt -- Part IV. The Cycling Environment -- Chapter 11. Dealing With Heat Stress / Stephen S. Cheung -- Chapter 12. Air Pollution and Cyclists / Mike Koehle and Luisa Giles -- Chapter 13. Altitude and Hypoxic Training / Randall L. Wilber -- Chapter 14. Tackling the Hills / Hunter Allen -- Part V. Nutrition and Ergogenics -- Chapter 15. Cycling Nutrition / Dina Griffin -- Chapter 16. Feeding During Cycling / Dina Griffin -- Chapter 17. Hydration Science / Stacy Sims -- Chapter 18. Doping's Dark Past and a New Cycling Era / Mikel Zabala -- Part VI. Cycling Health -- Chapter 19. Epidemiology of Cycling Injuries / Victor Lun -- Chapter 20. Managing Common Cycling Injuries / Victor Lun -- Chapter 21. Fatigue and Overtraining / Romain Meeusen and Kevin De Pauw -- Chapter 22. Recovery Interventions / Shona L. Halson and Nathan G. Versey -- Part VII. Training Development and Assessment -- Chapter 23. Long-Term Athlete Development / Kristen Dieffenbach -- Chapter 24. Psychological Strategies for Team Building / Javier Horcajo and Mikel Zabala -- Chapter 25. Motivation and Mental Training / Jim Taylor and Kate Bennett -- Chapter 26. Assessing Cycling Fitness / James Hopker and Simon Jobson -- Chapter 27. Designing Training Programs / Paul B. Laursen, Daniel J. Plews, and Rodney Siegel -- Chapter 28. Training Periodization / Bent R. Rønnestad and Mikel Zabala -- Chapter 29. Using a Power Meter / Hunter Allen -- Chapter 30. Data Management for Cyclists / Dirk Friel -- Part VIII. Preparing to Race -- Chapter 31. Off-the-Bike Training / Bent R. Rønnestad -- Chapter 32. Respiratory Training / A. William Sheel and Carli M. Peters -- Chapter 33. Warming Up / Jose M. Muyor -- Chapter 34. Stretching / Jose M. Muyor -- Part IX. Racing Your Bike -- Chapter 35. The Science of Pacing / Chris R. Abbiss -- Chapter 36. Road Racing / Hunter Allen -- Chapter 37. Mountain Biking / Howard T. Hurst -- Chapter 38. Track Cycling / Chris R. Abbiss and Paolo Menaspa ̀-- Chapter 39. BMX / Manuel Mateo-March and Cristina Blasco-Lafarga -- Chapter 40. Ultradistance.
Includes bibliographical references
Keywords: Cycling -- Training; Bicycle racing -- Training; Cycling -- Physiological aspects